2022
DOI: 10.2169/internalmedicine.8704-21
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to the BNT162b2 mRNA Vaccine in Healthcare Workers in a General Hospital in Japan: A Comparison of Two Assays for Anti-spike Protein Immunoglobulin G

Abstract: Objective This study assessed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody responses to the BNT162b2 mRNA vaccine in Japanese healthcare workers. Methods In this prospective cohort study, participants received two doses of the BNT162b2 mRNA vaccine on days 0 and 21 and provided blood for anti-SARS-CoV-2 antibody testing before the first vaccine and on days 21 and 35 after vaccination. Anti-spike protein immunoglobulin G (S-IgG) was measured using Abbott and Fujirebio chemiluminescent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The results obtained using the investigated methods correlated strongly ( Figure 2 ). The correlation between the immunoassays was previously reported by other researchers [ 31 , 32 , 33 , 34 ]; however, the strength of correlation varies between the papers, which may be attributed to the different timepoints investigated, the samples’ dilutions, and conversion to BAU/mL. Three of the methods included in our study were also compared by Lukaszuk et al in a similar group of vaccinees.…”
Section: Discussionsupporting
confidence: 75%
“…The results obtained using the investigated methods correlated strongly ( Figure 2 ). The correlation between the immunoassays was previously reported by other researchers [ 31 , 32 , 33 , 34 ]; however, the strength of correlation varies between the papers, which may be attributed to the different timepoints investigated, the samples’ dilutions, and conversion to BAU/mL. Three of the methods included in our study were also compared by Lukaszuk et al in a similar group of vaccinees.…”
Section: Discussionsupporting
confidence: 75%
“…S-IgG titers were measured by the CLEIA method using Lumipulse in this study. A few studies were comparing the antibody titers measured by Lumipulse and other automated methods, 23 and also, it is not clear whether the antibodies have direct neutralizing activity against mutant strains, including the Omicron strain. It was reported that the neutralizing antibody titers and IgG antibody titers correlate.…”
Section: Discussionmentioning
confidence: 99%
“…The serum samples were stored at −35 • C and tested for SARS-CoV-2 antispike (S) IgG using a commercial chemiluminescence enzyme immunoassay (SARS-CoV-2 S-IgG reagents, Fujirebio, Tokyo, Japan). This test had a specificity of 100 and a 98.7% concordance with the Abbott SARS-CoV-2 S-IgG assay (Abbott Japan LLC, Tokyo, Japan) [8]. If COVID-19 infection was suspected during the study period, participants were tested for SARS-CoV-2 via nasopharyngeal swab samples using a polymerase chain reaction test (ID NOW COVID-19, Abbott Japan LLC) [8].…”
Section: Methodsmentioning
confidence: 99%